The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/toxins14020129
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Botulinum Neurotoxin Subtypes A4 and A5 Cell Binding Domains in Complex with Receptor Ganglioside

Abstract: Botulinum neurotoxins (BoNT) cause the potentially fatal neuroparalytic disease botulism that arises due to proteolysis of a SNARE protein. Each BoNT is comprised of three domains: a cell binding domain (HC), a translocation domain (HN), and a catalytic (Zn2+ endopeptidase) domain (LC). The HC is responsible for neuronal specificity by targeting both a protein and ganglioside receptor at the neuromuscular junction. Although highly toxic, some BoNTs are commercially available as therapeutics for the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The quality of the electron density map is good throughout except for a small loop region (Arg 1269-Phe 1277). This loop (which is conserved across all BoNT/A subtypes) precedes the ganglioside binding site (GBS) and appears to be disordered for other H C /A subtypes [ 28 , 29 ]. This is likely due to the inherent flexibility of this loop so that it can accommodate ganglioside binding.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the electron density map is good throughout except for a small loop region (Arg 1269-Phe 1277). This loop (which is conserved across all BoNT/A subtypes) precedes the ganglioside binding site (GBS) and appears to be disordered for other H C /A subtypes [ 28 , 29 ]. This is likely due to the inherent flexibility of this loop so that it can accommodate ganglioside binding.…”
Section: Resultsmentioning
confidence: 99%
“…The program Dyndom [ 30 ] revealed a large hinge rotation of ~16.8° in H C /A6 (crystal form II) when compared to H C /A6 (crystal form I) and H C /A6:GD1a ( Figure 4 ). To date, this is the largest “hinge motion” in subdomain orientation observed among BoNT/A subtype structures [ 25 , 27 ], and it suggests a high degree of flexibility existing between the H CN and H CC subdomains. The biological implication of this hinge-rotation has not yet been determined; however, it has been previously suggested that it may aid in orientating the H N towards the membrane in preparation for translocation [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was observed previously for H C /A2, H C /A3, and H C /A5. Furthermore, H C /A6 forms seven hydrogen bonds with GD1a at Sia 5 , Gal 4 , and GalNAc 3 through six residues that are conserved among all BoNT/A subtypes (Figure 2) [23][24][25][26][27]. The H C /A6:GD1a interface is most similar to H C /A5, forming a total of 7 hydrogen bonds with the three monosaccharides GalNAc 3 , Gal 4 and Sia 5 [27].…”
Section: New Crystal Form Of H C /A6mentioning
confidence: 99%
See 1 more Smart Citation
“…During the simulation, we found that in addition to GBS, gangliosides also interact with BoNT/A1 via a structure that we referred to as the Ganglioside Binding Loop “GBL”, referring to the appellation used in previous studies 41, 42 . The GBL is defined by the amino acid sequence 1253-HQFNNIAK-1260 for which H1253 was identified to interact with ganglioside 43 . After performing a structural alignment of the heavy chain of BoNT/A1, BoNT/E1 and BoNT/F1, we observed that the GBL is not conserved in serotype E1 and F1 ( figure 7 C and D ).…”
Section: Discussionmentioning
confidence: 99%